Penetrating Head Injury by a Hit of Rake in a Child: A Case Report and Literature Review - Issa Ibrahim Assoumane; Nicaise Kpègnon Agada; Rabiou Maman Sani; Aminath Kélani (Case Reports in Neurological Medicine)
Background. A penetrating head injury (PHI) refers to a situation where a projectile has breached the cranium but does not exit it. It constitutes about 0.4% of all head injuries. Several nonmissile materials inserting the skull have been reported. But to our knowledge, never before has any case of PHI caused by a hit of rake been reported. We report a first case of PHI caused by a rake in a child; then, we relate our experience with its management and discuss the relevant literature. Cases Description. A 5-year-old boy has been admitted with a rake embedded in his head. That occurred during a violent play with a neighbor. At presentation, the child was alert; there was no neurological deficit. The rake was embedded in the parietal regions on each side of the midline. The head Computed Tomography (CT) scan performed showed a biparietal hyperdensity from either side of the midline with a metal artifact. In the operating room, after a transversal incision joining the 2 tips of the object, we performed successively bone flaps; object extraction; debridement; duraplasty; and closing. The outcome was uneventful. Conclusion. This is the first case of PHI by a rake. The surgical management constitutes the main challenging point.